Barriers and Strategic Solutions for the Adoption of Sustainable Concrete in Developing Countries: A Case Study of Tobruk, Libya - Ahmed Fathi Mohammed Labeedi; Abdullah Abdulsalam Abdullah Abkhatirh (African Journal of Advanced Pure and Applied Sciences, 2026)
The construction sector significantly contributes to global carbon emissions and resource depletion, with concrete production alone accounting for 8–9% of anthropogenic CO₂ emissions worldwide. Despite the environmental and economic benefits of sustainable concrete, its adoption remains limited in many developing countries, including Libya. This study aims to identify and assess the critical barriers hindering sustainable concrete adoption in Tobruk, Libya, and propose strategic solutions tailored to the local context. A quantitative approach was employed, utilizing a structured questionnaire distributed to 52 construction professionals, including civil engineers, project managers, contractors, and concrete industry employees. Nineteen barriers were identified from the literature and classified into four categories: knowledge and awareness, economic and resources, technical and implementation, and regulatory and cultural barriers. Data was analyzed using descriptive and inferential statistics, including Mean Item Score (MIS) and Kruskal-Wallis tests. Results revealed that knowledge and awareness barriers were not critical (MIS 2.23–3.71), while economic and resource barriers (MIS 3.46–3.79), technical and implementation barriers (MIS 3.54–3.79), and regulatory and cultural barriers (MIS 3.23–3.81) were significantly influential. The most critical barriers included lack of demonstration projects (MIS 3.81), low demand for sustainable materials (MIS 3.79), shortage of skilled labor (MIS 3.79), passive industry culture (MIS 3.79), and high material costs (MIS 3.77). Based on these findings, strategic solutions were developed across four categories, including financial incentives, workforce development, research and development funding, and regulatory reform. This study contributes to the limited body of knowledge on sustainable concrete adoption in North Africa and provides actionable recommendations for policymakers, construction professionals, and stakeholders in similar developing contexts.